(untitled) (Research, Society and Development, 2021)
Some chronic metabolic diseases are caused by eating disorders. In this aspect, the intestinal microbiota participates effectively, directly and indirectly, in various processes carried out in this environment, contributing to the homeostasis of the organism and in the regularization of these nutritional disorders. Recently, studies published in recent years have increasingly demonstrated the role of these microorganisms in the gastrointestinal tract and how they can act as probiotics, such as the bacteria Akkermansia muciniphila, which is interconnected with various biochemical and physiological processes. Thus, this work aimed to carry out an integrative review to compile information regarding the action of the A. muciniphila bacteria against metabolic dysfunctions. For this purpose, a scientific survey was carried out using a digital database, namely: PubMed (https://pubmed.ncbi.nlm.nih.gov/), ScienceDirect (https://www.sciencedirect.com/) and Google Scholar (https://scholar.google.com/). From the prospection, 14 articles on the subject were selected. Despite it, according to the scientific literature, the efficiency of A. muciniphila acting on behalf of the organism was evidenced in order to prevent and/or treat metabolic disorders resulting from diets rich, mainly in fat - a factor that can lead to obesity and, consequently, diabetes.